2002
DOI: 10.1046/j.1365-2044.2002.02821.x
|View full text |Cite
|
Sign up to set email alerts
|

Cp50 of propofol for laryngeal mask airway insertion using predicted concentrations with and without nitrous oxide

Abstract: SummaryThis study sought to determine the predicted Cp50 of propofol required for laryngeal mask airway insertion (Cp50LMA) and to investigate whether nitrous oxide reduces these required concentrations. Using target-controlled infusion and incorporating the standard Diprifusor TM pharmacokinetic model, 46 unpremedicated patients were randomly assigned to one of two groups. The patients received either 40% oxygen in air (control group: n ¼ 23), or 60% nitrous oxide in oxygen (nitrous oxide group: n ¼ 23). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…We reported previously that the levels of propofol Cp 50 for cLMA insertion were estimated as 3.24 lg/mL [8]. This study showed almost identical results to those that we reported earlier for Cp 50 of cLMA.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We reported previously that the levels of propofol Cp 50 for cLMA insertion were estimated as 3.24 lg/mL [8]. This study showed almost identical results to those that we reported earlier for Cp 50 of cLMA.…”
Section: Discussionsupporting
confidence: 87%
“…Concentration of plasma 50% (Cp 50 ), the concentration at which there is a 50% chance that a patient will respond by moving, was estimated as 3.24 lg/mL for cLMA insertion [8].…”
Section: Introductionmentioning
confidence: 99%
“…Casati et al [21] revealed that LMA insertion with the Diprifusor TCI system at target plasma concentration of 6 μg/mL with 95% success rate. Kodaka et al [22] studied the target concentration of propofol required to prevent movement in 50% (Cp50) of propofol for LMA insertion, and calculated that the Cp50 for LMA insertion was 4.07 μg/mL. When the plasma concentration is targeted, the TCI machine will rapidly infuse propofol to increase the plasma concentration of propofol to the selected level.…”
Section: Discussionmentioning
confidence: 99%
“…The 178 K. Sintavanuruk, et al Schnider pharmacokinetic effective site TCI model [10] was found to have better speed of induction and hemodynamic stability than plasma target model [11,12]. Several studies demonstrated induction of anesthesia with different plasma target controlled infusion of propofol for LMA insertion [13][14][15]. However, there is no study to compare the standard bolus propofol induction with the effective site TCI for LMA insertion.…”
mentioning
confidence: 99%
“…However, the ED 95 is probably more relevant than the ED 50 in our current study, as patients need to be adequately anaesthetised for laryngeal mask airway insertion. We estimated ED 95 by simple extrapolation of the logistic regression curve, which resulted in larger confidence intervals [17].…”
Section: Discussionmentioning
confidence: 99%